Cu–Zn disorder and band gap fluctuations in Cu2ZnSn(S, Se)4: Theoretical and experimental investigations (Phys. Status Solidi B 2/2016). Issue 2 (February 2016) - Scragg, Jonathan J. S.; Larsen, Jes K.; Kumar, Mukesh; Persson, Clas; Sendler, Jan; Siebentritt, Susanne; Platzer Björkman, Charlotte
Abstract : Cu2 ZnSn(S, Se)4 is a compound semiconductor that is in development for solar cells based on earth‐abundant materials. Scragg et al. (pp.247‐254 ) examine one of the troubling issues with this material, which is cation disorder in the crystal structure. The authors attempt to quantify the cation disorder using a physical model, thereby estimating the defect density that it causes. Then, they present calculations of the band structure that indicate much larger band gap fluctuations arising from cation disorder than had previously been considered: this could be a serious problem for the open circuit voltage obtainable from Cu2 ZnSn(S, Se)4 ‐based solar cells. Experiments using Raman spectroscopy and photoluminescence combined with in‐situ heat‐treatments confirm that the energy of the dominant band‐to‐band recombination pathway correlates perfectly to the progress of the order‐disorder transition. These results suggest that elimination of cation disorder could be key to future improvements in the efficiency of this type of solar cell.